2013
DOI: 10.1371/journal.pone.0058558
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plasma FL Expression with Bone Marrow Irradiation Dose

Abstract: PurposeAblative bone marrow irradiation is an integral part of hematopoietic stem cell transplantation. These treatment regimens are based on classically held models of radiation dose and the bone marrow response. Flt-3 ligand (FL) has been suggested as a marker of hematopoiesis and bone marrow status but the kinetics of its response to bone marrow irradiation has yet to be fully characterized. In the current study, we examine plasma FL response to total body and partial body irradiation in mice and its relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Pentraxin 3 (PTX3), a biomarker associated with vascular injury to the brain but previously unassociated with radiation exposure was also included in this study (2). FL is a cytokine known to induce proliferation and differentiation of bone marrow stem cells of myeloid and lymphoid origin and has recently been described as a biomarker of radiation exposure (3). The apolipoprotein SAA is a major acute phase reactant protein playing a central role in the inflammatory response and has been characterized as a marker of radiation exposure in heterogeneous radiation exposure profiles (46).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentraxin 3 (PTX3), a biomarker associated with vascular injury to the brain but previously unassociated with radiation exposure was also included in this study (2). FL is a cytokine known to induce proliferation and differentiation of bone marrow stem cells of myeloid and lymphoid origin and has recently been described as a biomarker of radiation exposure (3). The apolipoprotein SAA is a major acute phase reactant protein playing a central role in the inflammatory response and has been characterized as a marker of radiation exposure in heterogeneous radiation exposure profiles (46).…”
Section: Introductionmentioning
confidence: 99%
“…Flt3 Ligand, SAA, MMP9 and FGB were selected based on our previous studies which identified these proteins as being radiation responsive (3, 4). FL and SAA have also been previously characterized in other biodosimetry studies modeling total-body irradiation (TBI) and partial-body irradiation (PBI) (5, 810).…”
Section: Introductionmentioning
confidence: 99%
“…Partial-body exposures have also been shown to correlate with plasma expression of SAA, FL and G-CSF using a murine model ( 34 , 35 ). These studies were able to show relative increases in expression of plasma biomarkers correlating to an increasing area of partial-body exposure ( 26 , 36 ).…”
Section: Proteomicsmentioning
confidence: 94%
“…For example, several studies have shown that expression of cytokine FL, exhibits a direct relationship to the amount of radiation and has been used previously in clinical assessment of accidental exposures. (34, 36, 43). While a single marker or small panel of proteomic markers to determine dose has great utility for dose assessment, further proteomics studies are needed to evaluate internal exposures, other types of radiation exposure and preexisting clinical confounders.…”
Section: Proteomicsmentioning
confidence: 99%
“…Serum Flt3 ligand has been shown to reflect hematopoiesis at the progenitor cell level, increasing with the severity of bone marrow failure and normalizing as patients recover; it inversely correlated with colony forming ability in patient bone marrow cells [22]. Flt3 ligand may be a surrogate marker of decreased bone marrow hematopoietic potential as the hematopoietic stem cells (HSCs) are depleted, similar to the elevated Flt3 ligand levels seen after bone marrow irradiation [23], continued exploration of Flt3 ligand levels in the setting of GATA2 deficiency may help track or predict disease evolution [21*]. …”
Section: Disease Coursementioning
confidence: 99%